Mycorrhizae in Seven Exotic Coniffers Growing in New Forest - Mukherji, S. K.; Thapar, H. S. (Indian Forester, 1961)
The mycorrhizae have been described in Pinus caribaea, Araucaria bidwilli, A. cunninghamii, Agathis palmerstoni, Podocarpus neriifolius, P. gracilior and Cupressus torulosa, which are growing as exotics in New Forest. In P. caribaea, the mycorrhiza is ectotrophic, in others endotrophic. The introduction of an exotic becomes necessary when it serves a purpose not met with by the native species. While climatic and edaphic factors, among others are important, mycorrhiza is considered to be necessary in the successful establishment of the exotic in its new home. The mycorrhizal status of species of exotic conifers growing in the Forest Research Institute, New Forest, Dehra Dun forms the subject of the present study. The history of their introduction is given wherever available. There is no record about the introduction of the mycorrhizal fungus nor soil from the natural stand along with the seed.